PERAN FILSAFAT PENDIDIKAN ISLAM DALAM MENDIDIK KECERDASAN EMOSIONAL ANAK: THE ROLE OF ISLAMIC EDUCATIONAL PHILOSOPHY IN EDUCATING CHILDREN'S EMOTIONAL INTELLIGENCE - Lubab Khoirul Adib (Jurnal Intelek Insan Cendikia, 2024)
This study aims to determine the role of Islamic educational philosophy in improving children's emotional intelligence. The type of research used was library research, namely collecting data from various existing studies that are relevant to the problem. The data collection method uses library studies, namely variable data used from more than 1 source in the form of books or journals. Islamic Educational Philosophy is a fundamental thing that must be instilled in children even before they take their first education. This is because children's emotions can worsen if they are not instilled with the values of educational philosophy from an early age, which will result in children rebelling or arguing with their parents. Therefore, this study seeks to provide solutions to existing problems.